Corporate Social Responsibility programs analysis PT.Pertamina Indonesia in the era of pandemic Covid-19 - fadinah, Fadinah (Universitas Ahmad Dahlan, 2022)
This research aims to explains the CSR programs of PT. Pertamina during the covid-19 pandemic. Corporate Social Responsibilty (CSR) is a program within a company. CSR is not only an effort to show the concern of an organization on social and environmental issues, but also can be a supporter of sustainable development by weighing economic aspects and social development supported by environmental protection. In order to respond to change and create relationships of trust, the efforts now implemented by organizations (especially business organizations) are designing and developing a series of programs that lead to forms of social responsibility. For this reason, the author will discuss the CSR program of PT. Pertamina. Based on existing data, the author will explain the CSR program conducted by PT. Pertamina during the COVID-19 pandemic. Among them is a program to maintain food security by providing trainers to the built community about hydroponic plants. As well as training and economic empowerment programs for creative youth who are members of various MSME business groups in Walahar Village, Klari Subdistrict, Karawang Regency in the Era of the COVID-19 Pandemic by CSR PT. Pertamina (persero) Fuel Terminal Cikampek.